Endoparasites in domestic animals surrounding an Atlantic Forest remnant, in São Paulo State, Brazil - Sevá,Anaiá da Paixão (2018)
Abstract Morro do Diabo State Park (MDSP) is a significant remnant of the Atlantic Rain Forest in Brazil and is surrounded by rural properties. In that area, wild and domestic animals and humans are in close contact, which facilitates the two-way flow of infectious diseases among them. We assessed endoparasites in domestic livestock from all rural properties surrounding MDSP. There were sampled 197 cattle, 37 horses, 11 sheep, 25 swine, 21 dogs, one cat and 62 groups of chickens from 10 large private properties and 75 rural settlements. Eimeria spp. was present in almost all hosts, excepted in horses, dogs and cats. Giardia cysts were present only in cattle. Nematodes were found in swine, ruminants and horses in high prevalence. Ancylostoma, Toxocara and Sarcocystis were found in dogs. Chickens were found with coccidia, Ascaridida and Capillaria spp.. These parasites can cause malnutrition and reproductive disorders for their hosts. Strategies to prevent and control the spread of endoparasites can improve wildlife, animal and human health in this area.